Cryotherapy Improves Limb Use But Delays Normothermia Early After Stifle Joint Surgery in Dogs - Szabo, Stephanie D.; Levine, David; Marcellin-Little, Denis J.; Sidaway, Brian K.; Hofmeister, Erik; Urtuzuastegui, Erica (Frontiers in Veterinary Science, 2020)
Objective: To evaluate the short-term efficacy and safety of cold compression therapy (CCT) relative to a soft padded bandage (SPB) in dogs undergoing surgery to manage cranial cruciate ligament injury. Methods: Dogs were randomized into groups that received CCT or SPB after surgery. Weight bearing was measured using a weight distribution platform before and the day after surgery. Stifle joint flexion and extension were measured using a goniometer before and the day after surgery. Rectal temperatures were measured every fifteen minutes for 2 hours after surgery and the morning after surgery. Mechanical nociceptive thresholds (MNT) were measured using an algometer the day after surgery. Findings in both groups were compared using a mixed model ANOVA. Results: 20 dogs were enrolled: 10 in the CCT and 10 in the SPB group. Dogs undergoing CCT had more stifle joint flexion (P = 0.008) and weight bearing (P < 0.001) after surgery than dogs with SPB. MNT after surgery correlated statistically with stifle joint flexion after surgery (r = -0.315, P = 0.014), extension after surgery (r = 0.310, P = 0.016), and weight bearing after surgery (r = 0.314, P = 0.003). Return to normothermia was delayed in the CCT group, with temperatures approximately 0.5°C (1.0°F) lower 105 (P = 0.018) and 120 minutes (P = 0.013) after surgery. Conclusion: Relative to bandaging, CCT had a positive short-term impact on stifle flexion and weight bearing. CCT delayed warming after surgery but dogs were only mildly hypothermic (0.5°C [1.0°F]).